2016
DOI: 10.1103/physrevlett.117.176602
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall Effect and Origins of Nonlocal Resistance in Adatom-Decorated Graphene

Abstract: Recent experiments on the spin Hall effect (SHE) in graphene with adatoms, reporting unexpectedly large charge-to-spin conversion efficiency, have raised a fierce controversy. Here, we apply numerically exact Kubo and Landauer-Büttiker formulas to realistic disordered models of golddecorated graphene (including adatom segregation) to compute the spin Hall conductivity and spin Hall angle, as well as the nonlocal resistance which is directly measured in experiments. Large spin Hall angles of ≃ 0.1 are obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 76 publications
2
83
1
Order By: Relevance
“…28,[52][53][54][55][56][57][58][59][60][61][62][63][64] In this paper we present a detailed symmetry analysis focusing on effective SOC Hamiltonians in a way that is complementary to Refs. [40,56,65].…”
Section: Introductionmentioning
confidence: 99%
“…28,[52][53][54][55][56][57][58][59][60][61][62][63][64] In this paper we present a detailed symmetry analysis focusing on effective SOC Hamiltonians in a way that is complementary to Refs. [40,56,65].…”
Section: Introductionmentioning
confidence: 99%
“…Nonlocal signals detected in H-shape graphene structures decorated with metallic particles have been interpreted as due to large spin Hall effects, owing to SOC by proximity effects [33]. Theoretical analysis suggests that the proximity SOC should indeed enhance the spin Hall effect [34,35], but also that the signal in the H-shape structures can be affected by non spin-related contributions, which can lead to incorrect interpretations [35,36]. More recent experiments using a ferromagnetic source/detector [7,[10][11][12] in multilayer graphene/Pt spin devices demonstrated large spin signals at room temperature, showing the potential of graphene-based devices for spin to charge conversion [37].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent theoretical study showed the presence of a large R NL in Au-decorated graphene even in the absence of SOC [24]. They also reported that the spin Hall angle (θ SH ) in Au-clustered graphene can significantly fluctuate according to the applied gate voltage [24].…”
Section: Introductionmentioning
confidence: 95%
“…Kaverzin and van Wees also reported the absence of the field-induced effect in R NL for hydrogenated graphene and questioned the origin of previously reported R SHE NL [23]. Further, a recent theoretical study showed the presence of a large R NL in Au-decorated graphene even in the absence of SOC [24]. They also reported that the spin Hall angle (θ SH ) in Au-clustered graphene can significantly fluctuate according to the applied gate voltage [24].…”
Section: Introductionmentioning
confidence: 96%